New Hadamard Type Inequalities for Modified h-Convex Functions - Daniel Breaz; Çetin Yildiz; Luminiţa-Ioana Cotîrlă; Gauhar Rahman; Büşra Yergöz (Fractal and Fractional, 2023)
In this article, we demonstrated various Hermite–Hadamard and Fejér type inequalities for modified h-convex functions. We showed several inequalities for the products of two modified h-convex functions. New identities related to inequalities in various forms are also established for different values of the <semantics>h(φt)</semantics> function. We believe that the approach presented in this paper will inspire more research in this area.